Glucose tolerance in cystic fibrosis. Issue 5 (May 1991) - Lanng, S; Thorsteinsson, B; Erichsen, G; Nerup, J; Koch, C
Abstract : Glucose tolerance was evaluated in 356 living and dead patients with cystic fibrosis who were recorded at the Danish Cystic Fibrosis Centre. Twenty two patients (6%) were treated elsewhere, 25 (7%) were unable, unwilling or too young (age less than 2 years) to participate; 309 patients (87%) were therefore eligible for the study of whom 99 (32%) were dead and 210 (68%) were alive. Of the dead patients, 13 also had diabetes mellitus (13%). Of the living patients (median age 14 years, range 2-40), nine (4%) were known to have diabetes and all were being treated with insulin. In the remaining 201 patients an oral glucose tolerance test (1.75 g/kg body weight, maximum 75 g) was carried out. A total of 155 patients (74%) had normal glucose tolerance, 31 (15%) had impaired glucose tolerance, and 15 (7%) had diabetes mellitus according to the WHO criteria. The percentage of glycated haemoglobin (HbA1c) (reference range 4.1-6.4%) increased significantly as glucose tolerance decreased: when glucose tolerance was normal the median was 5.2%; when it was impaired the figure was 5.5%; in patients whose diabetes was diagnosed by the oral glucose tolerance test it was 5.9%; and in patients already known to have diabetes mellitus it was 8.6%. The incidence and prevalence of impaired glucose tolerance and diabetes mellitus increased with age. From the age of 15 to 30 years the decrease in the prevalence of normal glucose tolerance was almost linear. Within this age span the proportion of patients with cystic fibrosis with normal glucose tolerance was reduced by roughly 5%/year. Only 35% (95% confidence interval (CI) 22 to 48%) of the patients with cystic fibrosis who were alive at the age of 25 years had normal glucose tolerance; 32% (95% CI 14 to 49%) were diabetic. The prevalence of glucose intolerance in cystic fibrosis is rapidly increasing with age; its potentially harmful effect on the prognosis of cystic fibrosis is of increasing importance as the length of survival of these patients increases.